GAIT SPEED ASSOCIATED WITH CLINICAL FACTORS IN THE ELDERLY IN PRIMARY HEALTH CARE: INTEGRATIVE REVIEW - Spekalski, Midiã Vanessa dos Santos; Boldt, Paola; Domingues, Maria Paula Santos; Silva, Juliane Gomes da; Hammerschmidt, Karina Silveira de Almeida; Lenardt, Maria Helena; Betiolli, Susanne Elero (Cogitare Enfermagem, 2024)
Objective: to analyze national and international scientific production on gait speed associated with signs, symptoms, and clinical factors in elderly people in primary health care. Method: integrative literature review carried out in five data sources (Virtual Health Library, Embase, Web of Science, Cumulative Index To Nursing And Allied Health Literature (CINAHL), and PubMed) with publications from January 2017 to June 2023. Results: 13 publications met the eligibility criteria, with a predominance of studies in English. Studies indicated that reduced gait speed is associated with fractures (p<0.05), dementia (p<0.01), cardiovascular (p<0.001) and neuropsychiatric (p<0.01) diseases, falls (p<0.05) and polypharmacy (p<0.001). Conclusion: altered gait speed patterns in the older people are related to various clinical factors, reinforcing the need for further studies and the guiding role of the geriatric nursing team in the health of the older person.